We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website.
Please click on "Accept cookies" if you agree to the setting of cookies. Cookies that do not require consent remain unaffected by this, see
cookie policy and privacy policy.
DECLINE COOKIES

1.) It takes max three times as long as Felix to complete the same job. When the men work together, they can complete the job in 9 hours. how many hours are required for max to do the job alone?

2.) Solve the equation [x] / [x-2] = [4] / [x^2-8x+12] - [1] / [x-6]

which statements are true of the solutions(s) to the equation?

Select each correct answer:

a.) there are two accecptable soutions to the equation.

b.) There are no accecptable solutions to the equation.

c.) 6 is an extraneous solution because it creates a 0 in the denominator

d.) there is one acceptable solution to the equation

e.) 2 is an extraneous solution because it creates a 0 in the denominator.

whosmans Oct 19, 2018

#1**+1 **

1.) It takes max three times as long as Felix to complete the same job. When the men work together, they can complete the job in 9 hours. how many hours are required for max to do the job alone?

Let the portion of the job that Felix can complete in one hour = 1/x

Let the portion of the job that Max can complete in one hour = 1 / [3x]

So..... rate * time = potion of job done....so

Portion that Felix can do in 9 hours + portion that Max can do in 9 hrs = 1 job done

(1/x) (9) + ( 1 / [3x] ) (9) = 1

9/x + 3/x = 1

12/x = 1

x = 12 means that Felix can complete the whole job in 12 hours working alone

So..Max can complete the job in 3(12) = 36 hours working alone

CPhill Oct 19, 2018

#2**+1 **

2.) Solve the equation [x] / [x-2] = [4] / [x^2-8x+12] - [1] / [x-6]

x / [ x - 2] = 4 / [ ( x -6 ) ( x - 2) ] - 1/ (x - 6)

Multiply through by (x - 6) ( x - 2)

x ( x - 6) = 4 - ( x - 2 ) simpify

x^2 - 6x = 4 - x + 2

x^2 - 6x = 6 - x

x^2 - 5x - 6 = 0 factor

( x - 6) ( x + 1) = 0 set both factors to 0 and solve for x and we have that

x = 6 or x = -1

The first solution makes a denominator = 0....so it is extraneous

So.....

c.) 6 is an extraneous solution because it creates a 0 in the denominator

d.) there is one acceptable solution to the equation

CPhill Oct 19, 2018